Closed-form multi-dimensional solutions and asymptotic behaviors for subdiffusive processes with crossovers: I. Retarding case. (November 2021) - Awad, Emad; Sandev, Trifce; Metzler, Ralf; Chechkin, Aleksei
Highlights: We present higher-dimensional solutions to the distributed-order time-fractional diffusion equation modelling the crossover between two anomalous-diffusion regimes, here the retarding case is analysed. We derive closed-form solutions and demonstrate their positivity. Asymptotic behaviours at short and long times are discussed. Abstract: Numerous anomalous diffusion processes are characterized by crossovers of the scaling exponent in the mean squared displacement at some correlations time. The bi-fractional diffusion equation containing two time-fractional derivatives is a versatile mathematical tool describing specifically retarded subdiffusive transport, in which the scaling exponents acquires a smaller value, i.e., the diffusion becomes even slower after the crossover. We here derive closed-form multi-dimensional solutions for this integro-differential equation in n spatial dimensions by generalizing the classical Schneider-Wyss solution of the fractional diffusion equation with a single fractional derivative. In the two-dimensional case we develop a limiting approach based on the solution of the space-time fractional diffusion equation. The probabilistic interpretation in higher dimensions is discussed. The asymptotic long- and short-time behaviors are derived. It is shown that the solution of the bi-fractional diffusion equation can be interpreted in terms of the Fox H -transform of the Gaussian distribution.